Thermodynamic and environmental analysis for multi-component supercritical thermal fluid generation by supercritical water gasification of oilfield wastewater. (15th April 2023) - Peng, Zhiyong; Xu, Jialing; Rong, Siqi; Luo, Kui; Lu, Libo; Jin, Hui; Zhao, Qiuyang; Guo, Liejin
Abstract: Multi-component supercritical thermal fluid (MCSCTF) can be used to efficiently extract highly viscous heavy oil. However, few works have been conducted to explore MCSCTF generation at the system-level. In this paper, a novel process modeling for the MCSCTF generation system was developed based on the supercritical water gasification (SCWG) of oilfield wastewater. The life cycle assessment (LCA) methodology was employed to evaluate the environmental impact of the system. The use of segmented air supply and rational heat exchangers distribution to achieve process energetically self-sufficient, resulting in a 14.96% increase in exergy efficiency and 0.18 kg CO2 -eq/MJ exergy reduction in Global Warming Potential (GWP). The detailed exergy flows identified the high exergy destruction of the system, including heat transfer and air compression. The sensitivity analysis showed that increasing the compression stage, the heat transfer efficiency, and the MCSCTF temperature was conducive to improving the exergy efficiency and reducing the GWP. The exergy efficiency of 44.25% and GWP of 0.26 kg CO2 -eq/MJ exergy can be achieved by optimizing system parameters. Compared to other SCWG systems, this MCSCTF generation system is both efficient and eco-friendly. This work can provide essential theoretical guidance for the scale-up and design of the MCSCTF generation system. Graphical abstract: Image 1 Highlights: A novel MCSCTF generation energetically self-sufficient system was developed. The segmented air supply matching heat exchangers were used to increase energy efficiency. The heat transfer and air compression were the most exergy destruction process. The exergy efficiency of 44.25% and GWP of 0.26 kg CO2 -eq/MJ exergy can be achieved.